Maslinic Acid Enhances Docetaxel Response in Human Docetaxel-Resistant Triple Negative Breast Carcinoma MDA-MB-231 Cells via Regulating MELK-FoxM1-ABCB1 Signaling Cascade - Wang, Ke; Zhu, Xue; Yin, Yongxiang (Frontiers in Pharmacology, 2020)
Docetaxel (DOC) is the most important chemotherapeutic drug for the treatment of triple negative breast cancer (TNBC); however, acquired drug resistance upon the long-term treatment limits its therapeutic effect. Maslinic acid (MA), a natural triterpene from Olea europaea L., attracts increasing interest in recent years because of its promising anti-cancer activity, but the reversal effect of MA on drug resistance in cancer therapy is rarely explored. In this study, the combined effect of DOC and MA on human docetaxel-resistant triple negative breast carcinoma MDA-MB-231 (MDA-MB-231/DOC) cells was investigated. The enhanced effect of MA on DOC cytotoxicity and DOC accumulation was assessed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay and HPLC (high performance liquid chromatography) analysis in MDA-MB-231/DOC cells. Western blot, co-immunoprecipitation assay, luciferase reporter assay and chromatin immunoprecipitation (ChIP) assay were performed for exploring the underlying mechanisms. Our data indicated that the co-treatment of MA could dose-dependently enhance DOC sensitivity and cellular DOC accumulation in MDA-MB-231/DOC cells. Moreover, MELK-FoxM1-ABCB1 signaling cascade was confirmed to contribute to DOC resistance in MDA-MB-231/DOC cells. In such process, MA directly suppressed expressions and interaction of MELK and FoxM1 as well as the transcriptional activity of FoxM1, and thus reducing the expression of ABCB1. Overall, our study suggests that the combined use of DOC and MA may be helpful for overcoming DOC resistance in human TNBC therapy.